Математическая модель гидравлического сопротивления фильтра твердых частиц дизеля. Часть 1: настроечный коэффициент - Кондратенко, Александр Николаевич (НТУ "ХПИ", 2014)
Приведена и описана математическая модель гидравлического сопротивления фильтра твёрдых частиц (ФТЧ) в реальных условиях эксплуатации. Модель построена на основе расходной характеристики одного модуля ФТЧ, экспериментально полученной при постоянной температуре текучей среды, и данных стендовых испытаний автотракторного дизеля 2Ч10,5/12, оснащенного полноразмерным ФТЧ. Модель позволяет учесть ряд факторов, характеризующих условия эксплуатации ФТЧ в составе выпускной системы этого дизеля. Учет этих факторов производится путем введения соответствующих коэффициентов. В данной части работы описан физический смысл и оценены значения настроечного коэффициента модели, позволяющего связать результаты исследований на безмоторной установке и моторном стенде и учесть тип конструктивного исполнения модуля фильтрующего элемента

The paper deals with the mathematical model describing hydraulic resistance of a DPF under real operating conditions. The model is based on the flow characteristics of a single module of the DPF filter element obtained experimentally for a constant temperature of fluid, and data of bench tests of au-totractor diesel 2Ch10.5/12 equipped with a full-sized DPF. The model also allows taking into account a number of factors that characterize operating conditions of the DPF in the exhaust system of this di¬esel by introducing respective coefficient. The dependence of these coefficients on the operating and design parameters of diesel 2Ch10.5/12 is experimentally obtained and described using the method of linear regression. In this part of the research we describe the physical meaning and evaluate the adjust¬ing coefficient of this mathematical model, which allows to correlate the results of non-motorized in¬stallation studies and those obtained using engine test band, and to take into account the case design type of the DPF filter element module. Using flow characteristics of the exhaust stream, such as mass flow rate per unit area of the inlet section of the module, when designing a DPF allows taking into ac¬count the model dimensions of the model and the number of the filter element modules
Mathematical model of the hydraulic resistance of a diesel particulate matter filter. Part 1: adjusting coefficient
Keywords: температура; выпускная система; моторный стенд; фильтрующий элемент; diesel; particulate matter filter; hydraulic resistance; mathematical model